Azulenylcarbenes: Rearrangements on the C11H8 Potential Energy Surface. Issue 35 (12th July 2016) - Henkel, Stefan; Pollok, Corina H.; Schleif, Tim; Sander, Wolfram
Abstract: Four isomeric azulenylcarbenes were synthesized in argon matrices by photolysis of the corresponding diazo precursors, and the photochemistry of these carbenes was studied. The carbenes and their rearranged products were characterized by IR, UV/Vis, and EPR spectroscopy, and the experimental data were compared to results from DFT calculations. While 2‐, 5‐ and 6‐azulenylcarbene show triplet ground states, 1‐azulenylcarbene exhibits a singlet ground state, in accord with theoretical predictions. The rearrangements of the azulenylcarbenes give access to a number of unusual C11 H8 isomers, such as other carbenes and strained allenes. Abstract : Center of attention : The spin state and the singlet–triplet splitting of the isomeric azulenylcarbenes depends on the position of the carbene center at the azulene system. 1‐Azulenylcarbene has a singlet ground state, while the 2‐, 5‐ and 6‐carbenes are triplet ground state molecules. The carbenes were isolated and characterized in low temperature argon matrices (see figure).